Corporate Groups Between Doctrinal Construction and Operational Articulation: A Legal-Analytical Inquiry - Tienti, Meriem (Journal of Legal Studies and Researches, 2026)
The study examines the legal and structural configuration of Algerian corporate groups, revealing a complex economic concentration mode characterized by judicial plurality and centralized control. Despite the absence of codified regulation in the Commercial Code, corporate groups are recognized through fiscal legislation, particularly Article 138 bis of the Direct Tax Code. The paper examines the legal autonomy of companies and the functional dominance of parent entities, analyzing control modes like equity-based, governance-oriented, and pyramidal to understand operational dynamics and regulatory asymmetries. The study advocates for a comprehensive legal framework that encapsulates intra-group governance economic realities, promoting transparency, corporate coherence, and institutional accountability.